Answer:
n = 59
Step-by-step explanation:
The given equation of n is
and we have to solve it for n.
........... (1)
⇒
{Rationalizing the numerator}
⇒
.............. (2)
Now, adding (1) and (2) we get
⇒ n + 5 = 64 {Squaring both sides}
⇒ n = 59 (Answer)
Looks like your function is
![f(x)=\dfrac x{6x^2+1}](https://tex.z-dn.net/?f=f%28x%29%3D%5Cdfrac%20x%7B6x%5E2%2B1%7D)
Rewrite it as
![f(x)=\dfrac x{1-(-6x^2)}](https://tex.z-dn.net/?f=f%28x%29%3D%5Cdfrac%20x%7B1-%28-6x%5E2%29%7D)
Recall that for
, we have
![\dfrac1{1-x}=\displaystyle\sum_{n=0}^\infty x^n](https://tex.z-dn.net/?f=%5Cdfrac1%7B1-x%7D%3D%5Cdisplaystyle%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20x%5En)
If we replace
with
, we get
![f(x)=\displaystyle x\sum_{n=0}^\infty\frac(-6x^2)^n=\sum_{n=0}^\infty (-6)^n x^{2n+1}](https://tex.z-dn.net/?f=f%28x%29%3D%5Cdisplaystyle%20x%5Csum_%7Bn%3D0%7D%5E%5Cinfty%5Cfrac%28-6x%5E2%29%5En%3D%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20%28-6%29%5En%20x%5E%7B2n%2B1%7D)
By the ratio test, the series converges if
![\displaystyle\lim_{n\to\infty}\left|\frac{(-6)^{n+1} x^{2(n+1)+1}}{(-6)^n x^{2n+1}}\right|=6|x^2|\lim_{n\to\infty}1=6|x|^2](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Clim_%7Bn%5Cto%5Cinfty%7D%5Cleft%7C%5Cfrac%7B%28-6%29%5E%7Bn%2B1%7D%20x%5E%7B2%28n%2B1%29%2B1%7D%7D%7B%28-6%29%5En%20x%5E%7B2n%2B1%7D%7D%5Cright%7C%3D6%7Cx%5E2%7C%5Clim_%7Bn%5Cto%5Cinfty%7D1%3D6%7Cx%7C%5E2%3C1)
Solving for
gives the interval of convergence,
![|x|^2](https://tex.z-dn.net/?f=%7Cx%7C%5E2%3C%5Cdfrac16%5Cimplies%7Cx%7C%3C%5Cdfrac1%7B%5Csqrt6%7D%5Cimplies%20-%5Cdfrac1%7B%5Csqrt%206%7D%3Cx%3C%5Cdfrac1%7B%5Csqrt%206%7D)
We can confirm that the interval is open by checking for convergence at the endpoints; we'd find that the resulting series diverge.